Analisis Penerapan E-Court Dalam Sistem Peradilan Perdata di Indonesia Guna Mewujudkan Peradilan yang Transparan - Tsabitha, Andara; Rahmadhani, Aulia; Pebrianti, Kalista Revana; Zakaria, Salsabila Anggraini (Media Hukum Indonesia (MHI), 2024)
Along with the rapid digital transformation in various aspects of people's lives, the need to reform the legal system towards digitalization is becoming increasingly urgent. So that the establishment of e-Court in Indonesia is an important response to this development. Therefore, this article is compiled with the aim of finding out more about the urgency of the establishment of e-Court and its application in the civil justice system in Indonesia. The method used in this writing is to use the normative legal method, which prioritizes library materials. Finally, it can be concluded that the Establishment of e-Court is based on various Supreme Court regulations, starting from Supreme Court Regulation Number 3 of 2018 to Supreme Court Regulation Number 7 of 2022, as a form of reform in the field of information technology in the justice system. This e-Court system accelerates the judicial process by utilizing technology, but in its implementation, not all parties have adequate access or technological capabilities, so that it can cause gaps in the implementation of justice.